2018
DOI: 10.2147/cmar.s161007
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus laparoscopic gastrectomy with D2 lymph node dissection for advanced gastric cancer: a propensity score-matched analysis

Abstract: BackgroundRobotic gastrectomy (RG) is a new surgical method alternative for gastric cancer. However, few studies have evaluated the outcomes of RG for advanced gastric cancer (AGC). Thus, the aim of this study was to compare the short-and long-term outcomes of RG and laparoscopic gastrectomy (LG) with D2 lymph node dissection for AGC.Patients and methodsWe retrospectively evaluated 454 patients with AGC who underwent RG or LG with D2 lymph node dissection for AGC between August 2013 and March 2017. The short-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 47 publications
0
43
0
Order By: Relevance
“…After a thorough review of the full text of the 10 papers, one paper was excluded because it was a letter [13], and another study was excluded because the survival data were insufficient for analysis [14]. Finally, eight papers were included for our meta-analysis [15][16][17][18][19][20][21][22]. The study selection process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After a thorough review of the full text of the 10 papers, one paper was excluded because it was a letter [13], and another study was excluded because the survival data were insufficient for analysis [14]. Finally, eight papers were included for our meta-analysis [15][16][17][18][19][20][21][22]. The study selection process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Only one study reported DFS results [16]; there was no significant difference between the two groups in DFS, the HR was 1.08 with a 95% CI from 0.26 to 4.44, and the P value was 0.67. Four studies [15][16][17]20]. A meta-analysis of the four studies indicated that the two techniques had similar RFS outcomes (HR, 0.92; 95% CI, 0.72-1.19; P = 0.53).…”
Section: The Primary Outcomesmentioning
confidence: 96%
See 3 more Smart Citations